2021
DOI: 10.1038/s42003-021-01723-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic analysis of rodent models reveals conserved and species-specific modulators of human sarcopenia

Abstract: Sarcopenia, the age-related loss of skeletal muscle mass and function, affects 5–13% of individuals aged over 60 years. While rodents are widely-used model organisms, which aspects of sarcopenia are recapitulated in different animal models is unknown. Here we generated a time series of phenotypic measurements and RNA sequencing data in mouse gastrocnemius muscle and analyzed them alongside analogous data from rats and humans. We found that rodents recapitulate mitochondrial changes observed in human sarcopenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 92 publications
11
56
0
Order By: Relevance
“…We chose two months of age to replicate a prior study [ 20 ] and to capture a metabolic snapshot at the beginning of adulthood, when rapid postnatal muscle growth begins to stabilize [ 21 , 22 ]. We chose 21-months as the beginning of old age, when loss of muscle mass and function begins due to age-associated sarcopenia [ 20 , 23 ]. We collected tissues under basal metabolic conditions at ZT6 (zeitgeber time 6, noon) after a 4 h fast and during the normal physiological fasting + rest phase for nocturnal mice [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…We chose two months of age to replicate a prior study [ 20 ] and to capture a metabolic snapshot at the beginning of adulthood, when rapid postnatal muscle growth begins to stabilize [ 21 , 22 ]. We chose 21-months as the beginning of old age, when loss of muscle mass and function begins due to age-associated sarcopenia [ 20 , 23 ]. We collected tissues under basal metabolic conditions at ZT6 (zeitgeber time 6, noon) after a 4 h fast and during the normal physiological fasting + rest phase for nocturnal mice [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to humans, we found declines in locomotor activity ( Figure 12B ), gait velocity ( Figure 12C ), and grip strength ( Figure 12D ); these declined at younger relative ages in male mice compared to humans. Age-related changes in grip strength assessed by the four-limb wire hanging test is controversial ( DeanIII, Scozzafava et al, 1981 ; Graber et al, 2013 ; Shoji et al, 2016 ; Börsch et al, 2021 ), however, several studies have demonstrated that these physical traits apparently deteriorate in aged mice ( DeanIII, Scozzafava et al, 1981 ; Benice et al, 2006 ; Serradj and Jamon, 2007 ; Graber et al, 2013 ). DeanIII, Scozzafava et al (1981) showed, for example, that performance in the wire-hang test begins to decline between 23 and 31 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, rigorous argument might be required when comparing the gait of bipedal human and sedentary mice. Together with possible contribution of body weight ( Oellrich et al, 2016 ) and muscle mass ( Börsch et al, 2021 ), further careful studies using other tests ( Hoffman and Winder, 2016 ; Takeshita et al, 2017 ) are necessary to determine that grip strength progressively decline with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of mice, those ranging from 18 to 24 months-of-age, which is comparable to humans of 56 – 69 years-of-age, fulfil the requirements of “young-old” age, whereas mice aged 26 months and older can be considered as “old-old” [ 10 ]. It is notable that 22 – 24 months of age is when morphological changes consistent with human sarcopenia [ 11 ] commence in mice and rats [ 12 , 13 ]. This is the period skeletal muscle mass and grip strength decline progressively with age, exhibiting prominent changes at 24-28 months of age, while whole–body mass and lean mass were relatively stable or only marginally declined [ 13 ].…”
Section: Introductionmentioning
confidence: 99%